2013
DOI: 10.1115/1.4023893
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling and Multi-Objective Optimization of a Mini-Channel Heat Exchanger Via Genetic Algorithm

Abstract: In the present paper a mathematical model for a mini-channel heat exchanger is proposed. Multiobjective optimization using genetic algorithm is performed in the next step in order to obtain a set of geometrical design parameters, leading to minimum pressure drops and maximum overall heat transfer coefficient. Multiobjective optimization procedure provides a set of optimal solutions, called Pareto front, each of which is a trade-off between the objective functions and can be freely selected by the user accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…An optimal rib width is obtained for a given pitch width by changing rib width to achieve the maximum cell current density [47]. Our previous study demonstrated that the optimal rib width is only sensitive to the rib-electrode contact resistance and pitch width [19,21].…”
Section: Expressions For the Optimal Rib Widthsmentioning
confidence: 99%
“…An optimal rib width is obtained for a given pitch width by changing rib width to achieve the maximum cell current density [47]. Our previous study demonstrated that the optimal rib width is only sensitive to the rib-electrode contact resistance and pitch width [19,21].…”
Section: Expressions For the Optimal Rib Widthsmentioning
confidence: 99%
“…It is found as the result of the MCDM problem that a set of alternatives which are A (10) , A (9) , and A (8) was found as the best choices. This implies that A (10) , A (9) , and A (8) have no superiority over another and therefore one of them can be regarded as optimum solution. These alternatives are highlighted in Table 1.…”
Section: Multiple-criteria Decision-making (Mcdm)mentioning
confidence: 99%
“…Finally, they concluded that entropy generation and maximum temperature of mini-channel heat sink have the same effect on optimization results, and there is not a unique optimum. Selleri et al [10] obtained a mathematical model for a mini-channel heat exchanger under laminar flow conditions using the analytical and numerical results available in the literature aiming to find optimal mini-channel exchanger design for various operating conditions. Then, they validated these mathematical models and used them for optimization problem definition.…”
Section: Introductionmentioning
confidence: 99%
“…Vividly, a perfect solution which can satisfy all of the objectives at the same time, does not exist. Therefore, a logical alternative for dealing with a multi-objective problem is to determine a set of solutions, each of which satisfies the objectives at a suitable level while not being dominated by any other solution [19]. In case all of the objective functions should be minimized, a feasible solution x is said to dominate another feasible solution y , if and only if , for i = 1,…,K and for least one objective function j.…”
Section: Humidifier Finite Difference Equationsmentioning
confidence: 99%
“…A solution is called Pareto optimal if it is not dominated by any other solution in the considered space [19]. Evolutionary algorithms, specifically genetic algorithm (GA), with their unique capabilities for this kind of problems, are promising methodologies for dealing with multiobjective optimization problems [19][20].…”
Section: Humidifier Finite Difference Equationsmentioning
confidence: 99%